Kajian pendegradan asid askorbik dalam admikstur pemakanan parenteral - Ahmad Fuad Shamsuddin,; Risydan Mohamad,; Bukhori Abu Bakar, (penerbit ukm, 2004)
This study was carried out to investigate the influence of storage time, storage temperature and oxygen on degradation of ascorbic acid in parenteral nutrition admixture (PNA). The PNAs were prepared in ethyl vinyl acetate (EVA) bags based on basic parenteral nutrition regimen. The PNAs were prepared aseptically in a laminar flow hood. Storage temperature was set at 25, 30, 35 and 40°C. Samples containing air (oxygen) and air-free were taken from EVA bags at 0, 6, 12, 24 and 30 hrs. PNA samples (containing ascorbic acid) were analysed by High Performance Liquid Chromatography (HPLC). Standard calibration curve and retention time of ascorbic acid were determined prior to analysis of samples. The study showed a significant decrease of ascorbic acid content in both PNAs containing air and air-free in relation to the increase in storage time and temperature (p < 0.05). The decrease of ascorbic acid content in PNAs with air was higher compared to the ones air-free. In conclusion, the degradation of ascorbic acid in PNAs is influenced by storage time and temperature as well as the presence of air.